First record of Xiphinema globosum Sturhan, 1978 (Nematoda: Longidoridae) from Croatia - Barsi, László (Biologia Serbica, 2023)
The discovery of a population of Xiphinema globosum in a soil sample collected in 2012 at Horvatove stube, Medvednica Mt. represents the first recording of this species in Croatia. This population is briefly described, illustrated, and morphometric data for females, males and four juvenile developmental stages are presented. Previous findings for this species are discussed and commented.